THE CONSTITUTION IN THE NEW EDITION: NEW APPROACHES AND NEW LAW PRACTICE (IN THE EXAMPLE OF HUMAN AND CITIZEN'S RIGHTS AND FREEDOMS GUARANTEES) - Shokir Atayev (American Journals Publishing, 2023)
This article explores the new edition of the constitution, focusing on innovative approaches and legal practices that enhance the guarantees of rights and freedoms for individuals and citizens. It delves into the importance of updating constitutional frameworks to adapt to societal changes and the evolving needs of the people. By examining the implementation of safeguards for human rights and citizenship, the article sheds light on how these provisions serve as a model for ensuring the protection and promotion of fundamental liberties in contemporary society.
Keywords: New edition of the constitution, Approaches to constitutional, reform, Legal practices, Rights and freedoms, Human rights guarantees, Citizenship rights, Constitutional safeguards, Constitutional adaptation, Evolving societal needs, Protection of fundamental liberties.